Marketing Strategy of Mushroom Baglog in UMKM Agro Jamur Lombok, Gunungsari Sub-District, West Lombok - Fadli, Fadli; Jupri, Ahmad; Kuncoro, Zain Bagus; Rozi, Tapaul; Hidayati, Lilik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
White oyster mushroom is one of the most widely cultivated mushrooms in Indonesia because it has a high economic value. Umkm Agro Mushroom Lombok is one of the oyster mushroom and mushroom baglog cultivation businesses in West Lombok district. Apart from oyster mushrooms, in Umkm, mushroom baglogs also have a fairly high economic value with the right marketing and marketing strategy. One of the analytical tools that can be used in designing a marketing strategy is SWOT analysis. This analysis is able to identify strengths, weaknesses, opportunities and threats. The method in this study uses descriptive methods with data sources that come from direct sources or primary data and come from other sources or secondary data. The results of the analysis using SWOT show that quality and service are the strengths of Agro Mushroom Lombok, while the lack of promotion and baglogs that are vulnerable to weather are weaknesses, the potential that can be utilized is customer loyalty and a fairly wide market reach. The threats faced are the emergence of new competitors and limited raw materials. The strategies that can be applied are by prioritizing product quality so that the level of customer loyalty increases, besides that it is necessary to intensify promotion through social media to increase market reach.